Auctions with In-house Bids - Greve, T. (Portuguese Economic Meeting, 2023)
The US government was front-runner in the employment of in-house bidding in public procurement tenders, known as A-76 competitions. In 2009, this type of competitions was prohibited due to a number of concerns, including uncertainty with regard to cost savings. We study a tender where an in-house unit competes with external private bidders. In equilibrium, the in-house bidder bids its true competitive cost, generating cost savings for the government (/buyer). Under a scenario of information revelation regarding the competing bids to the in-house bidder, the equilibrium strategy of the in-house bidder remains unchanged, and so this information does not translate into an advantage for the in-house bidder, or the buyer. Under a collusion scenario, the in-house bid serves as an upper bound to the collusive bid, lowering its value (reaching a bounded collusion effect).